O acesso aos medicamentos na atenção primária à saúde em Belo Horizonte - Fernanda de Castro Aquino (2015)
The drugs are indispensable for maintaining and restoring people’s health, but access to them is still restricted for a large portion of the world population. As a gateway to the Unified Health System (SUS), the Primary Health Care is presented as the best site for obtaining essential drugs. This research had as object of study the access to medicines in Primary Health Care (APS) in the city of Belo Horizonte. Proposes in its aims to evaluate the availability of the medicines in Health Centers (CS); identify the difficulties found by prescribers related to pharmaceutical assistance (AF) in Belo Horizonte; identify the strategies used by the user on obtaining the drugs; evaluate how the user is hosted at the pharmacy of CS; identify the main causes of non-delivered drugs to users of CS; check the existence of a guidance to the user on the use and conservation of medicines. This is an exploratory research, of qualitative approach, on a case study format. It was selected three CS with different characteristics, in Venda Nova region, located in Belo Horizonte. For data collection, different techniques that complement each other were utilized: Pharmacy observation and semi-structured interviews with doctors and users. The results point out that in the three CS researched most of the user population has access to medicines, even though there are periods of shortages with certain frequency, making it difficult not only the doctors’ activities, but also the care continuity. It was observed that the pharmacy's hosting system to the user is most often indifferent, damaging a more humanized care. Rarely it was observed guidance on the right use and conservation of medicines. This study suggests that the AF of Belo Horizonte City Hall succeeds on meeting most prevalent demands of the user population, however still requires some adjustments to make the medicines fully accessible. Further studies in this area are important to verify a greater extent of the presented results.